2013
DOI: 10.1177/0956797613493444
|View full text |Cite
|
Sign up to set email alerts
|

War’s Enduring Effects on the Development of Egalitarian Motivations and In-Group Biases

Abstract: In suggesting that new nations often coalesce in the decades following war, historians have posed an important psychological question: Does the experience of war generate an enduring elevation in people's egalitarian motivations toward their in-group? We administered social-choice tasks to more than 1,000 children and adults differentially affected by wars in the Republic of Georgia and Sierra Leone. We found that greater exposure to war created a lasting increase in people's egalitarian motivations toward the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
180
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(202 citation statements)
references
References 34 publications
17
180
5
Order By: Relevance
“…While more research is needed to explore this issue, our ndings are also broadly consistent with eld experiments such as Gumen (2012) and Buchan et al (2009) who nd ingroup biases in similar designs using naturally-occurring group identities, as well as with previous work suggesting a link between parochialism and violent con ict (Choi and Bowles, 2007;Voors et al, 2012;Bauer et al, 2014). The fact that we nd a similar e ect in a neutrally-framed laboratory setting suggests that the mere act of competition over a xed-resource increases in-group bias, even in the absence of underlying ethnic divisions, cultural stereotyping, or exposure to violence.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While more research is needed to explore this issue, our ndings are also broadly consistent with eld experiments such as Gumen (2012) and Buchan et al (2009) who nd ingroup biases in similar designs using naturally-occurring group identities, as well as with previous work suggesting a link between parochialism and violent con ict (Choi and Bowles, 2007;Voors et al, 2012;Bauer et al, 2014). The fact that we nd a similar e ect in a neutrally-framed laboratory setting suggests that the mere act of competition over a xed-resource increases in-group bias, even in the absence of underlying ethnic divisions, cultural stereotyping, or exposure to violence.…”
Section: Discussionsupporting
confidence: 87%
“…In line with this theoretical prediction, recent empirical evidence on the e ects of war on social preferences shows that war leads to more altruism towards neighbors (Voors et al, 2012), stronger egalitarian norms towards in-group members by children (Bauer et al, 2014), and more within-group cooperation (Gneezy and Fessler, 2012).…”
Section: Related Literaturementioning
confidence: 56%
“…In one example, shortly after being challenged with a standardized laboratory stressor male participants took economic decisions indicative of increased trust, trustworthiness, sharing 192 and altruistic punishment 193 . Other studies in civilian populations of countries engaged in war conflicts suggested that the well-known phenomenon of increased societal in-group cooperation in times of war might not be a direct, immediate reaction of the individuals but rather a result of group pressure 194 and early life programming 195 .…”
Section: Box 1 Stress and Social Behaviors In Humansmentioning
confidence: 99%
“…Miguel and Roland 2011). In fact, several studies have found that exposure to civil conflict increases political engagement (Bellows andMiguel 2009, Blattman 2009), enhances cooperation and pro-sociality (Voors, Nillesen, Verwimp, Bulte, Lensink, andVan Soest 2012, Bauer, Cassar, Chytilová, andHenrich 2013), and makes people more willing to bear profitable risks (Voors, Nillesen, Verwimp, Bulte, Lensink, andVan Soest 2012, Callen, Isaqzadeh, Long, andSprenger 2014).…”
Section: Introductionmentioning
confidence: 99%